Nonislet Cell Tumor Hypoglycemia in a Patient with Adrenal Cortical Carcinoma - Se Won Kim; Seung-Eun Lee; Young Lyun Oh; Seokhwi Kim; Sun Hee Park; Jae Hyeon Kim (Case Reports in Endocrinology)
Nonislet cell tumor hypoglycemia (NICTH) is a rare but serious paraneoplastic syndrome in which a tumor secretes incompletely processed precursors of insulin-like growth factor-II (IGF-II), causing hypoglycemia. Here, we report an exceptional case of NICTH caused by nonfunctioning adrenocortical carcinoma in a 39-year-old male with recurrent hypoglycemia. The patient’s serum IGF-II/IGF-I ratio had increased to 27.8. The serum level of the IGF-II/IGF-I ratio was normalized after removal of the tumor, and the hypoglycemic attacks no longer occurred after the operation.